Core occupations as a building block for European vocational education and training - Heß, Erik [Verfasser]; Spöttl, Georg [Verfasser] (My University, 2009)
"At present, the proposals for a European Qualification Framework (EQF) and for a Credit Point System in Vocational Education and Training (ECVET) are revitalising the discussion surrounding European core occupations, although it remains unclear whether occupations should play a role in this system and which "vocational education and training concept" could form the basis of consensus in Europe. Core occupations may constitute the foundation for the respective context of a sector related "ECVET configuration" and could provide a major contribution to a vocational education and training concept dialogue between social partners and policymakers. The present paper investigates whether the establishment of European core occupations represents an opportunity to enrich the European vocational education and training debate by adding a modern concept of vocationalism." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 2.2.1 Ordnung von Ausbildungsberufen; L 1.1 Curriculumformen; Europäischer Kernberuf; Europäisches Leistungspunktesystem; Beruflichkeit; Berufsbild; Arbeitsprozessorientierung